Synthesis of surface nano-molecularly imprinted polymers for sensitive baicalin detection in biological samples. Issue 52 (10th June 2015) - Gu, Xiaoli; He, Hongliang; Wang, Chong-zhi; Gao, Yankun; Zhang, Hongjuan; Hong, Junli; Du, Shuhu; Chen, Lina; Yuan, Chun-su
<x xml:space="preserve">Abstract</x> Schematic representation of the possible process of MIP@SBA-15.